The Nonlinear Dynamic Behaviors of Electrostatic Micro-Tweezers (Communications in Computational Physics, 2018)
This work addresses the nonlinear dynamic behavior of different electrostaticmicro-tweezers, a micro electric actuator. This actuator, a cantilever beam electrostaticmicro-tweezers, has been extensively used in micro-electro-mechanical systems(MEMS). The importance of micro electric actuators manufactured is higher than theother part of MEMS since it is the power source of the entire micro-electro-mechanicalsystems. In actual operation, the instability and bad dynamic characteristics of the electricactuators will cause larger displacement mobility error, such as transport behaviorand response procedures failure, etc., and even damage the micro-electro-mechanicalsystems. To improve the actuator dynamic displacement accuracy, the dynamic behaviorin the electric actuator system must be studied, especially for nonlinear dynamicbehavior of system. In this work, the differential quadrature method (DQM) was employedto solve the problem of nonlinearity in the equation of motion. The resultsreveal that the proposed DQM model can be used to simulate the nonlinear behaviorof the micro-tweezers efficiently. Micro-tweezers of various shapes were studied to examinethe feasibility of applying the DQM in analyzing their nonlinear responses. Thesimulated results agree very closely with the calculated and experimental data in theliterature.